Engaging Community Health Centers (CHCs) in Research Partnerships: The Role of Prior Research Experience on Perceived Needs and Challenges. Issue 2 (April 2014) - Beeson, Tishra; Jester, Michelle; Proser, Michelle; Shin, Peter
Abstract Despite community health centers' substantial role in local communities and in the broader safety‐net healthcare system, very limited research has been conducted on community health center research experience, infrastructure, or needs from a national perspective. A national survey of 386 community health centers was conducted in 2011 and 2012 to assess research engagement among community health centers and their perceived needs, barriers, challenges, and facilitators with respect to their involvement in public health and health services research. This paper analyzes the differences between health centers that currently conduct or participate in research and health centers that have no prior research experience to determine whether prior research experience is indicative of different perceived challenges and research needs in community health center settings.